2022
DOI: 10.3390/microorganisms10040806
|View full text |Cite
|
Sign up to set email alerts
|

A New Early Predictor of Fatal Outcome for COVID-19 in an Italian Emergency Department: The Modified Quick-SOFA

Abstract: Background: Since 2019, the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is causing a rapidly spreading pandemic. The present study aims to compare a modified quick SOFA (MqSOFA) score with the NEWS-2 score to predict in-hospital mortality (IHM), 30-days mortality and recovery setting. Methods: All patients admitted from March to October 2020 to the Emergency Department of St. Anna Hospital, Ferrara, Italy with clinically suspected SARS-CoV-2 infection were retrospectively included in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The summary of quality assessment using PROBAST is shown in Table 2. Overall, 13 retrospective cohort studies (23)(24)(25)(28)(29)(30)(31)(32)(33)(34)36,41,45) had a high risk of bias, principally because we assumed that subjects had systematic differences in the accuracy of reporting past information, resulting in recall bias (51,52). The details of the quality assessment are recorded in Appendix 2.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The summary of quality assessment using PROBAST is shown in Table 2. Overall, 13 retrospective cohort studies (23)(24)(25)(28)(29)(30)(31)(32)(33)(34)36,41,45) had a high risk of bias, principally because we assumed that subjects had systematic differences in the accuracy of reporting past information, resulting in recall bias (51,52). The details of the quality assessment are recorded in Appendix 2.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Of note, a recent study by Guarino et al mentioned new scale of ICU admission prognosis score named modified quick SOFA score (Mq‐SOFA) to evaluate in‐hospital survival for COVID‐19 cases in Italy. 33 They defined Mq‐SOFA based on four parameters: SpO2/FiO2 ratio, respiratory rate ≥22/min, systolic blood pressure ≤100 mmHg, and considerable disorientation or confusion. By doing so, they found that Mq‐SOFA could reliably predict both in‐hospital mortality and 30‐day mortality with high levels of sensitivity (58.1% and 84.2%, respectively), and diagnostic accuracy (78.3% and 77.6%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Such risk factors should show high odds ratios in predicting mortality. Of note, a recent study by Guarino et al mentioned new scale of ICU admission prognosis score named modified quick SOFA score (Mq‐SOFA) to evaluate in‐hospital survival for COVID‐19 cases in Italy 33 . They defined Mq‐SOFA based on four parameters: SpO2/FiO2 ratio, respiratory rate ≥22/min, systolic blood pressure ≤100 mmHg, and considerable disorientation or confusion.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus Disease 2019 (COVID-19) is a life-threatening disease caused by the SARS-CoV-2 virus, and it was firstly reported in China and then spread worldwide [1]. Since the beginning of the COVID-19 pandemic, millions of patients have died because of complicated SARS-CoV-2 pneumonia [1][2][3]. The clinical features of COVID-19 range from an asymptomatic condition to severe/fatal lung injury and multi-organ failure.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical features of COVID-19 range from an asymptomatic condition to severe/fatal lung injury and multi-organ failure. Common complications include acute respiratory distress syndrome (ARDS), acute kidney and liver dysfunctions, delirium/encephalopathy, thrombosis, and cardiac damage (e.g., cardiomyopathy, arrhythmias, and sudden cardiac death) [1,2]. The severity of this condition suggested that pulmonary co-infections (e.g., Chlamydia pneumoniae, Mycoplasma pneumoniae, pneumococcus, or other agents, e.g., viruses) might have a role in worsening clinical manifestations of SARS-CoV-2 pneumonia [4].…”
Section: Introductionmentioning
confidence: 99%